2015
DOI: 10.1080/08964289.2015.1107525
|View full text |Cite
|
Sign up to set email alerts
|

A Mixed-Methods Pilot Study of Mindfulness-Based Stress Reduction for HIV-Associated Chronic Pain

Abstract: Treatment guidelines for chronic pain recommend non-pharmacologic modalities as part of a comprehensive management plan. Chronic pain is common among people living with HIV/AIDS, but there is little data to guide the choice of non-pharmacologic therapies in this complex population. We performed a mixed-methods feasibility study of Mindfulness Based Stress Reduction (MBSR) versus health education control with 32 inner city, HIV-infected participants. Outcome measures included: the Brief Pain Inventory, Perceive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 60 publications
0
17
0
Order By: Relevance
“…The control condition used in these nine studies was most often standard care (44%); four studies used an active comparison (e.g., brief version of MBSR; alternative stress-management intervention; time-matched education control; brief education and support) and one study included an assessment-only control. The four studies (52, 54, 58, 59) that used an active comparison group met for a median of 5 sessions of 90 minutes each. The median number of post-intervention follow-ups was two (range = 1 to 5); five studies measured outcomes at a single post-intervention assessment only (50, 54, 57, 60, 61).…”
Section: Resultsmentioning
confidence: 99%
“…The control condition used in these nine studies was most often standard care (44%); four studies used an active comparison (e.g., brief version of MBSR; alternative stress-management intervention; time-matched education control; brief education and support) and one study included an assessment-only control. The four studies (52, 54, 58, 59) that used an active comparison group met for a median of 5 sessions of 90 minutes each. The median number of post-intervention follow-ups was two (range = 1 to 5); five studies measured outcomes at a single post-intervention assessment only (50, 54, 57, 60, 61).…”
Section: Resultsmentioning
confidence: 99%
“…To the best of our knowledge, only 3 small RCTs have evaluated CBT and mindfulness-based treatment. 29 , 35 , 118 Nonrandomized trials of CBT 113 and hypnosis 25 have also been conducted. Further evaluation of psychosocial treatments for HIV and chronic pain is thus needed.…”
Section: Discussionmentioning
confidence: 99%
“…Some emerging research suggests benefits of mindfulness in underserved populations (e.g., Amaro et al 2014; Fuchs et al 2013; George et al 2015; Palta et al 2012; Roth and Robbins 2004). For example, older African American women indicated that a Mindfulness-Based Stress Reduction (MBSR) course helped them to cope with negative emotions, pain, and financial stress (Szanton et al 2011).…”
Section: Introductionmentioning
confidence: 99%